PENGAWASAN WARGA NEGARA ASING (WNA) OLEH KANTOR IMIGRASI KELAS II TANJUNG BALAI KARIMUN - Bromas Bani Wigo; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The immigration office is one of the technical executive units of immigration. The immigrations office has some areas in the organizational structure. In this study , the author focuses more on surveillance sections and immigration forms that deal directly with foreigners. The suerveillance activities being done by the second class immigration office Tanjung Balai Karimun containing administrative and field surveillance. The goal of this study is to find out the surveillance of a foreign citizen by second class immigration office Tanjung Balai Karimun, and to find out what factors affect the control of foreign nationals second class immigration office Tanjung Balai Karimun. The concept of a theoryused by Manullang, on a surveillance indicator referring to the three dimensions of surveillance, first establish the standards, conduct judgment actions, conduct repair actions. In this study a descriptive method with a qualitative approach .in data collection, researchers use interview techniques , observation and documentation using models Miles and Huberman . this research shows that the surveillance of a foreign citizen done by the second class immigration office Tanjung Balai Karimun are not properly and less effective because it is not done evenly and with a factor influencing the surveillance of foreign contriesare human resources, tools and infrastructure, community participation, and geography.Keyword : Management, Surveillance, Immigration Office